School Leadership Model in Supporting the Success of the School-Moving Program Management (A Study at PAUD PG-TK ASMAUL HUSNA in Bandung Regency) - Prihatini (Jurnal Ragam Pengabdian, 2026)
PG-TK Asmaul Husna is one of the early childhood education services in Rancaekek sub- district, Bandung Regency. PG-TK Asmaul Husna is one of 17 PAUD service institutions that became the 3rd batch of driving schools in Bandung District. SP PAUD is a collaboration program between the Ministry of Education and Culture and the local government. This PAUD Driving School includes steps intended to foster the quality of Early Childhood Education through various efforts of PAUD Principals. The objectives of this study are (1) to describe the principal leadership model applied by PG-TK Asmaul Husna. (2) describe the PSP that has been implemented by PG- TK Asmaul Husna. (3) describe the supporting and inhibiting factors in the management of PSP at PG-TK Asmaul Husna. This research uses descriptive qualitative research. The subjects of this study were the principal, representatives of PG, TK-A and TK-B teachers. The research method used with data collection using interviews, observation and documentation. Based on the results of research and discussion, it is found that (1) the principal's leadership model in PG-TK Asmaul Husna applies elements of eight leadership models, but there are three models that are more dominant in supporting the successful management of PSP, namely the situational leadership model, effective leader model and transformational leadership. (2) The PSP that has been implemented by PG-TK Asmaul Husna has activities that are in line with the objectives of the PSP. Such as Character Development, Numerical Development and Literacy. These activities can run well because the principal's leadership at PG-TK Asmaul Husna in leading uses three   more dominant models, namely the situational leadership model, the effective leader model and transformational leadership. (3) As for the supporting and inhibiting factors in the management of PSP at PG-TK Asmaul Husna, there are supporting factors such as assistance from the government, complete facilities, teachers and a supportive foundation. While the inhibiting factors are the need to learn a lot, work becomes more, and vacation time is consumed. Suggestions for Asmaul Husna PG-TK institutions are expected to be able to maintain and improve the leadership model that has been applied in managing the driving school program to make it even better.